2006
DOI: 10.1016/j.memsci.2006.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Properties of PEMs based on cross-linked sulfonated poly(ether ether ketone)

Abstract: PEMs prepared from sulfonated poly(ether ether ketone) and cross-linked with simple polyols (ethylene glycol and glycerol), exhibited enhanced strength, stability in hot water and high proton conductivity. The properties and chemical structure of the cross-linked membranes were studied using TGA, 1 H NMR and FTIR. These data suggest that ethylene glycol and glycerol molecules do not link neighbouring main chains via sulfonic acid functions, but rather form alcohol-ether oligomers, bonded to -SO 3 -group and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…In addition, differences between SO 2 and SO 3 [30] Mikhailenko et al have suggested that the release of CO 2 prior to the SO 2 release could indicate the formation of an electrophile (RSO 2 þ ) available for cross-linking via ipso or H-substitution, under the release of a hydroxyl radical that can directly react with the main chain. [27] However, as no further evidence for these degradation reactions is seen, and CO 2 that has been sorbed in the proton-rich watery environment present in the material cannot be excluded as alternative CO 2 sources, we consider this reaction unlikely in our system.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, differences between SO 2 and SO 3 [30] Mikhailenko et al have suggested that the release of CO 2 prior to the SO 2 release could indicate the formation of an electrophile (RSO 2 þ ) available for cross-linking via ipso or H-substitution, under the release of a hydroxyl radical that can directly react with the main chain. [27] However, as no further evidence for these degradation reactions is seen, and CO 2 that has been sorbed in the proton-rich watery environment present in the material cannot be excluded as alternative CO 2 sources, we consider this reaction unlikely in our system.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 94%
“…Previous studies on SPEEK decomposition only reported SO 2 release in a unimodal peak between 200 and 400 8C (a temperature shift of some tens of degrees could be the result of differences in heating rate), although not all studies include an evolved-gas analysis up to a temperature of 500 8C. [13,15,17,27] Scheme 1 summarizes the two possible routes for SO x loss from the material: protodesulfonation or ipso substitution. If a sulfone (R-SO 2 -R) bridge is formed by ipso substitution, this sulfone bridge can in turn decompose at higher temperatures, yielding the release of a second SO x species.…”
Section: Conversion Of Extinction Coefficient To Absorption Coefficientmentioning
confidence: 99%
“…The precipitated polymer (SPEEK) was washed several times until the pH of the wash water was 5. The polymer was subsequently dried in air at room temperature for 48 h and then dried in an oven at 60 C for 48 h, which resulted in clear, nonporous films [20,21].…”
Section: Preparation Of Membranesmentioning
confidence: 99%
“…Further, in aqueous environment at relatively high temperature (fuel cell operating temperature) SPEEK membrane swells extensively and as a result the mechanical property is not adequate enough to be useful for long-term application in fuel cells. Many research efforts have been undertaken to prepare more stable and mechanically strong membranes through crosslinking [9][10][11][12][13][14][15][16]. Crosslinking of sulphonated aromatic hydrocarbons can be achieved through bridging the reactive sulphonic acid group available in the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking of SPEEK has also been obtained by aliphatic/aromatic amines [12] and imide containing amines [13]. Advantages and disadvantages of such efforts have recently been elaborated [14,15]. Kaliaguine and co-workers carried out detailed study on crosslinking of SPEEK using glycol, glycerol and erythritol in different solvent/solvent pair [14].…”
Section: Introductionmentioning
confidence: 99%